2021
DOI: 10.5195/ijms.2021.958
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Canadian Narrative Review on the Protocols for COVID-19 and Canadian Emergency Departments

Abstract: First described in Wuhan, China, in December 2019, The World Health Organization declared the novel coronavirus disease (COVID-19) a global pandemic on March 11th, 2020. Canada identified its first positive COVID-19 patient on January 25th, 2020. The Canadian government and heath care system immediately started discussing how best to respond to this pandemic. It was hypothesized that potentially positive and confirmed positive COVID-19 patients would present to emergency departments across the country. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In the United States, national syndromic surveillance data reported that ED visits declined by 42% between April 2019 and April 2020 ( 2 ), and for paediatric hospitals in the United States, ED visit rates decreased by 45.7% over 2017 to 2019 versus 2020 ( 3 ). In Canada, ED visits declined by 50% between April 2019 and April 2020 ( 4 ) and the number of ED visits across Canada’s network of tertiary care paediatric centres decreased by 58% ( 5 ).…”
mentioning
confidence: 99%
“…In the United States, national syndromic surveillance data reported that ED visits declined by 42% between April 2019 and April 2020 ( 2 ), and for paediatric hospitals in the United States, ED visit rates decreased by 45.7% over 2017 to 2019 versus 2020 ( 3 ). In Canada, ED visits declined by 50% between April 2019 and April 2020 ( 4 ) and the number of ED visits across Canada’s network of tertiary care paediatric centres decreased by 58% ( 5 ).…”
mentioning
confidence: 99%